CO2 – Intrinsic Product, Essential Substrate, and Regulatory Trigger of Microbial and Mammalian Production Processes - Blombach, Bastian; Takors, Ralf (Frontiers in Bioengineering and Biotechnology, 2015)
Carbon dioxide formation mirrors the final carbon oxidation steps of aerobic metabolism in microbial and mammalian cells. As a consequence, CO2/HCO3− dissociation equilibria arise in fermenters by the growing culture. Anaplerotic reactions make use of the abundant CO2/HCO3− levels for refueling citric acid cycle demands and for enabling oxaloacetate-derived products. At the same time, CO2 is released manifold in metabolic reactions via decarboxylation activity. The levels of extracellular CO2/HCO3− depend on cellular activities and physical constraints such as hydrostatic pressures, aeration, and the efficiency of mixing in large-scale bioreactors. Besides, local CO2/HCO3− levels might also act as metabolic inhibitors or transcriptional effectors triggering regulatory events inside the cells. This review gives an overview about fundamental physicochemical properties of CO2/HCO3− in microbial and mammalian cultures effecting cellular physiology, production processes, metabolic activity, and transcriptional regulation.